The epitope of mouse embryonic antigen(s) recognized by monoclonal antibody TEC-02 is a carbohydrate carried by high-molecular-weight glycoconjugates - Dráber, P (Cell differentiation, 1987)
The expression and properties of mouse embryonic antigens, recognized by monoclonal antibody TEC-02, were analyzed in teratocarcinoma-derived cell lines. TEC-2 antigens were found in the majority of the parietal endoderm cells PYS-2 and in a fraction of cultured embryonal carcinoma cells but not in other cell lines tested. During the course of retinoic acid-induced differentiation of embryonal carcinoma cells F9, the expression of TEC-2 was transiently increased. Immunolabeling of extracts from F9 and PYS-2 cells separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed that TEC-2 antigens are polydisperse glycoconjugates of high molecular weight (mostly greater than 100,000). The TEC-2 epitope was shown to be carbohydrate which in F9 cells might be attached to the same carrier as another developmentally regulated carbohydrate epitope TEC-1. The TEC-2 antigens, isolated by indirect immunoprecipitation, were degraded by extensive pronase digestion or mild alkaline treatment to mostly large products. Immunostaining of glycolipid standards suggested that TEC-2 epitope involves the GalNAc beta 1----4Gal beta 1----4R sequence. Combined data indicate that TEC-2 is a new developmentally regulated carbohydrate epitope carried in embryonal carcinoma cells predominantly on glycoprotein-bound large carbohydrates.
Keywords: molekulová hmotnost; Cell Line; karcinoembryonální antigen; monoklonální protilátky; Carbohydrates; Teratoma; Molecular Weight; tretinoin; Epitopes; glykokonjugáty; Carcinoembryonic Antigen; epitopy; Glycoconjugates; Chromatography, Gel; teratom; Precipitin Tests; Tretinoin; Animals; Antibody Specificity; specificita protilátek; Detergents; zvířata; precipitinové testy; gelová chromatografie; myši; buněčné linie; sacharidy; Antibodies, Monoclonal; Mice; detergenty